THE COMPONENTS OF CORPORAL CULTURE OF MOVIMENT AS SEEN FROM THE POINT OF VIEW OF FUNDAMENTAL GRADE STUDENTS (Fiep Bulletin - online, 2013)
The objective of the  Physical Education in the School (PES)  is to transmit  to the students a contextualization of the  information given to them as well as  lead them to learn how to interact with their classmates, recognizing in this way which values support the universe of the culture of corporal movement productions (the games, plays, sports, dancing,  gymnastics and fighting, which have in common the body representation of several aspects of the human culture), these productions in the scope of  the school environment privilege the understanding of these practices as having cultural meaning and also that new forms of experimentation, opposing  the traditional ones, will bring to the student the possibility of give sense to the his or her own gestural field and so,  bringing to them a perception of themselves as agents.So, it is not enough to the PES to teach to the students the technicalities of movements, the basic skills or even, the physical capabilities, but it need to go beyond, and teach them the context in which the skills it teaches will appear, integrating in this way, the student in the scope of his or her own body culture movement. Objective: The objective that can be drawn from this research is to analyze the pedagogical practice of teachers at Visconde do Rio Branco – MG, as seeing by students, about the contents given to them in the classroom, analyzing their experience considering the contents of movement body culture. Methodology: This work is an exploratory research, in which the method used is the descriptive qualitative.270 students of 8th grade and 9th grade have participated in this research, of both sexes and coming from distinct social classes, from a municipal school belonging to the public net of the city of Visconde do Rio Branco MG. Conclusion: Thus we conclude that although the SPE is a body of knowledge with diversity and at the same time, richness, there is the possibility of its very transmission in the school room, but this is not what we observe in the vast majority of physical education classes. It is urgent that the remade of the body of knowledge promote the human emancipation, which as the research show us, as a matter of fact, seldom happens.
Keywords: Physical Education in the School (PES); Body Culture Movement; Content.